Characteristics of Patients Who Underwent Mastoidectomy: A Two Years Experience - Gunasekaran, Ashwini; Mahdiani, Sally; Veronica, Fifi (Althea Medical Journal, 2017)
Background: Mastoidectomy is a surgical procedure to remove an infected portion of the bone behind the ear called mastoiditis when medical treatment is not effective. Patients with chronic suppurative otitis media (CSOM) complications mostly need this surgery in order to maintain the normal function of hearing. Chronic mastoiditis and cholesteatoma are the most common indications of CSOM. This study was conducted to identify the characteristics of patients who underwent mastoidectomy at Dr. Hasan Sadikin General Hospital, from 2012â 2013.Methods: A descriptive study using total sampling method was conducted. Data were collected from medical records of 41 patients who underwent mastoidectomy at Dr. Hasan Sadikin General Hospital from 2012â2013. Inclusion criteria were medical records of patients whoÂ underwentÂ mastoidectomy, and consisted of variables studied, such asÂ age, gender, chief complaint, main etiology, method of surgery,Â and presence of abnormalities in the structure of middle ear. Incomplete medical records were excluded. The collected data were presented using percentage.Results: Age ranged from 15â64 years (85.37%), male patients were higher (65.9%) compared to female patients (34.1%). Otorrhea (70.73%) was the main chief complaint and infection (100%) was the main cause. Majority of patients had canal wall down (CWD) surgery (63.41%) and many abnormalities were found in the inner ear structure during the surgery.Conclusions: Infection is the only cause and otorrhea is the main indication for mastoidectomy. Most patients have been operated with CWD technique.Â